IMPLEMENTASI PENDIDIKAN HOLISTIK DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP - Lalu Diraja Hidayatullah; Fathurrahman Muhtar; Adi Fadli (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2024)
Islamic Religious Education at the secondary level is an integral part of the process of character-building and student spirituality. This study aims to identify the form of implementation of Holistic Education for SMPN 1 Batukilang students and the challenges it faces. The research method used is a qualitative approach with a qualitative descriptive approach. Data were collected through observation, interviews, and documentation, then analyzed through data reduction, data presentation, and conclusion drawing. The results showed that; (1) there are methods that have been applied in the implementation of holistic education, namely, providing examples, habituation, motivation, giving gifts, and the use of punishment, (2) there are several challenges in the implementation of holistic education, namely, association outside the school environment, the influence of social media, and the non-compliance of all students in implementing school rules. The findings have important value in improving Islamic religious education that is more holistic, positively impacts students' character development, and provides inspiration and guidance for other schools in their efforts to improve their religious education. Keywords: Implementation of Education, Holistic Education, Islamic Education Learning.